Childhood socioeconomic status modifies the association between intellectual abilities at age 20 and mortality in later life. Issue 11 (11th October 2009) - Kajantie, E; Räikkönen, K; Henriksson, M; Forsén, T; Heinonen, K; Pesonen, A K; Leskinen, J T; Laaksonen, I; Paile-Hyvärinen, M; Osmond, C; Barker, D J P; Eriksson, J G
Abstract : Background: People who score poorly in intellectual ability tests have shorter life expectancy. A study was undertaken to determine whether this association is different in people from different socioeconomic backgrounds. Methods: The mortality of 2786 men born in Helsinki, Finland during 1934–1944 who, as military conscripts, underwent a standardised intellectual ability test comprising verbal, visuospatial and arithmetic reasoning subtests was studied. Mortality data came from the Finnish Death Register. Results: Comparing men in the lowest and highest test score quartiles, HRs for all-cause mortality were 1.9 (95% CI 1.4 to 2.5) for verbal reasoning, 2.2 (95% CI 1.6 to 3.0) for visuospatial reasoning and 1.9 (95% CI 1.4 to 2.5) for arithmetic reasoning, corresponding to 2.6, 3.4 and 2.6 excess years of life lost, respectively. Associations were similar for cardiovascular and non-cardiovascular mortality. Intellectual ability scores were stronger predictors in men who grew up in middle-class families. Compared with middle-class men in the highest quartile of the visuospatial reasoning score, middle-class men in the lowest quartile lost 6.5 years of life while men from families of manual workers in the highest quartile lost 2.8 years and men in the lowest quartile lost 5.6 years. Conclusions: High intellectual ability in men aged 20 protects them from mortality in later life. This effect is stronger in men who grew up in middle-class families than in those who grew up in manual worker families. This finding suggests that early life conditions that are unfavourable to the development of cognitive abilities negate the life expectancy benefits of being born into a more affluent family.